HR-2 Mutations in Human Immunodeficiency Virus Type 1 gp41 Restore Fusion Kinetics Delayed by HR-1 Mutations That Cause Clinical Resistance to Enfuvirtide - Ray, Neelanjana (American Society for Microbiology (ASM), 2009)
Enfuvirtide (ENF) prevents the entry of human immunodeficiency virus type 1 (HIV-1) into cells by binding to the HR-1 region of the viral envelope (Env) protein gp41 subunit. Resistance to ENF arises via mutations in the drug binding site in HR-1. In addition, HR-2 mutations are commonly observed in ENF-resistant Env proteins, though their role remains unclear. We explored the mechanistic basis for clinical resistance to ENF and the role of HR-2 mutations. Using panels of ENF resistance-associated mutants for two patients, we found that mutations in HR-1 slowed the fusion kinetics and that mutations in HR-2 restored fusion rates. We assessed the differences in the rates of fusion of these mutants from a temperature-arrested state and observed similar trends, suggesting that the step of delay occurs after coreceptor engagement. Sensitivity to neutralizing antibodies was unchanged by the HR-1 and HR-2 mutants in each panel. Since this result was in contrast to those of a previous in vitro analysis where enhanced sensitivity to neutralization was demonstrated for heterologous Envs with ENF resistance-associated HR-1 changes, we examined the context dependence of HR-1 and HR-2 mutations by transferring the mutations seen in one patient into the Env context of another. These studies revealed that some, but not all, HR-1 mutations, when placed out of context (i.e., in a patient Env where they did not originally arise), enhance sensitivity to neutralizing antibodies. However, in most cases, HR-1 mutations in ENF-treated patients evolve in a manner that preserves pretreatment neutralization sensitivity so as to evade the pressures of the immune system.